What Is a Healthy Dating or Marriage Relationship? - Victor William Harris (EDIS)
Defining what a healthy romantic relationship is can be challenging. Thankfully, modern research has given us a good idea of what healthy dating and marriage relationships look like. Use this fact sheet to determine what a healthy relationship looks like to you. Then take the survey to get an idea of the strengths already present in your relationship and those things you may want to work on. This 3-page fact sheet was written by Victor W. Harris and published by the UF Department of Family Youth and Community Sciences, March 2013.